Rancang Bangun Aplikasi Game Edukasi Huruf, Angka Dan Gambar Pada Sekolah Mutiara Bagi Bangsa - Hermansyah, Pranata Yudistira; Setiawati , Popong (International Journal Labs, 2025)
Educational game applications have very high potential to increase motivation in the learning process. Apart from increasing motivation, educational games also have advantages compared to e-learning methods, they are easier to understand and more interesting. The design of this game will prioritize the teaching and learning process using the concept of